Design, Synthesis and Organocatalysis of 2,2′-Biphenol-Based Prolinamide Organocatalysts in the Asymmetric Direct Aldol Reaction in Water - Zhao, Hong-Wu; Sheng, Zhi-Hui; Meng, Wei; Yue, Yuan-Yuan; Li, Hai-Long; Song, Xiu-Qing; Yang, Zhao (Synlett, 2013)
In this work, 2,2′-biphenol-based prolinamide water-compatible C2- and C1-symmetrical organocatalysts were synthesized with the use of enantiopure N-Cbz-(S)-proline as chiral source. Under the optimal reaction conditions, the C1-symmetrical organocatalyst performed efficiently in the direct aldol reactions in water, thus delivering the desired aldol adducts in high yields (up to 100% yield) with excellent stereocontrol (up to 97:3 dr and 98% ee). The observed stereochemical outcome of the direct aldol reactions in water was interpreted by the proposed transition state.
Keywords: axially unfixed 2,2′-biphenol; prolinamide; water-compatible organocatalyst; aldol reaction; stereoselectivity